Genre Hybridization and the Representation of Heritage in Saradiq al-Hulm wa al-Faji'a by Azzedine Djelaoudji - Atoui, Atoui (El Omda in Linguistics and Discourse Analysis, 2025)
The article deals with the phenomenon of overlapping literary races in the Algerian novel, because the modern novelistic text is a problematic text This is what prompted us to search for the points of intertwining in the novel "The Survival of Dream and Bereavement" by Izz al-Din Jalawji, using it as a sample for this literary phenomenon, trying to extract the manifestations of the intersection of the novel with poetry, theater and folklore. Keywords: The novel, Overlapping races, Poetry, Theater ,Folklore .